2021
DOI: 10.1111/age.13105
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide DNA methylation and transcription analysis in tongue and biceps femoris muscles of cloned pigs with macroglossia

Abstract: Summary Cloned animals are prone to abnormal phenotypes such as enlarged tongue, fetal oversize, and progeria. In the present study, whole‐genome bisulfite sequencing and mRNA sequencing were performed on tongue and biceps femoris muscles of cloned piglets with and without macroglossia, in an attempt to elucidate the epigenetic causes of the macroglossia phenotype. We identified 14 958 and 18 752 differentially methylated regions in the tongue and biceps femoris muscles, respectively, of macroglossia piglets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…In the present study, we found some developmental defects including abnormal front legs, enlarged tongue, and hernia. We decided to analyze only enlarged tongue because that was the highest prevalence rate in a previous report by Yang et al [16]. As shown in Figure 4, we confirmed for the first time that the enlarged tongue from a cloned piglet exhibits very strange patterns of broken and isolated muscle bundles.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In the present study, we found some developmental defects including abnormal front legs, enlarged tongue, and hernia. We decided to analyze only enlarged tongue because that was the highest prevalence rate in a previous report by Yang et al [16]. As shown in Figure 4, we confirmed for the first time that the enlarged tongue from a cloned piglet exhibits very strange patterns of broken and isolated muscle bundles.…”
Section: Discussionsupporting
confidence: 68%
“…As described above in the introduction section, one of the reasons for decreasing the efficiency of cloning in pigs is developmental defects such as being overweight, giant forelimbs, atrophy of tendons, enlarged tongue, and exomphalos [13][14][15][16]. In the present study, we found some developmental defects including abnormal front legs, enlarged tongue, and hernia.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…For example, Lyu et al 28 discovered that chi-miR-487b-3p regulates goat myoblast growth by targeting IRS1 and affecting the PI3K/Akt signaling pathway, thereby inhibiting skeletal myogenesis. Liu et al 29 established that miR-124a functions as a regulatory factor for VMP1 in muscle tissue. Modulating the expression of miR-124a, either through overexpression or inhibition, can exert effects on myoblast proliferation and autophagy.…”
Section: Discussionmentioning
confidence: 99%